Implementasi Sistem Informasi Pembangunan Daerah (SIPD) dalam Perencanaan Pembangunan di Bappeda Kabupaten Kutai Timur - Devi Novita Sari (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The purpose of this study is to find out how the implementation of SIPD policies in regional development planning in Bappeda, East Kutai Regency. This study uses George C. Edward III's theory of policy implementation which aims to determine the success rate of SIPD policy implementation in the Bappeda of East Kutai Regency. The research method used is qualitative with a descriptive approach. The data collection needed is based on primary and secondary data from interviews, observations, documentation, which are analyzed to draw conclusions from the research problem. The findings of this study are that the implementation of SIPD has not been fully successful, because it only fulfills two indicators out of a total of four indicators of success. However, as a new policy, of course, Bappeda is already quite optimal in its implementation and will continue to be improved over time.